HANDLES OF CERAMIC VESSELS OF THE EARLY BRONZE AGE IN PRIMORSKY DAGESTAN (QUESTIONS OF TYPOLOGY AND CHRONOLOGY) - Budajciev, Arsen Lahmanovic (History, Archeology and Ethnography of the Caucasus, 2021)
The aim of the paper is a typological and chronological study of handles of ceramic vessels, originated from the well-investigated sites of the Early Bronze Age of Primorsky lowlands of Dagestan, including both the settlements (Velikent II, Gemeh-tubeh I, II, Kabaz-kutan I, II, Topakh-kala), and the burials (Velikent I (catacomb № 8), II (catacomb № 1), III (catacomb № 1), Karabudakhkent II, Kayakent VI)), as part of the areal of the Velikent culture of the Kuro-Araxes cultural-historical society. The earliest ceramic ware handles in the Northeast Caucasus are associated with the Eneolithic age. In the Early Bronze age, the handles become a characteristic part of the ceramic ware (dishes, containers, goblets, vases) among the sites of Primorsky Dagestan under consideration. Functionally, they have utilitarian, decorative-artistic and cult purpose. The handles can be classified into four types, typical for one or another form of ware: type 1 – horizontal-tubular, type 2 – ribbon-shaped, type 3 – pseudo-handles, type 4 – semi-spherical. The paper provides the description of each type of the handles along with the analogues on the sites of the Early Bronze Age both in the Northeast Caucasus and the adjacent regions of the Caucasus –the territories of modern Iran, Turkey, Palestine and Israel, which were part of the distribution area of the Kuro-Araxes cultural and historical society (including Khirbet Kerak culture). The work identifies the most common and earliest types of vessels, dating back to the Eneolithic period, and discusses the issue of their chronology. This article is a first special study devoted to a typological and chronological analysis of ceramic vessel handles.
Keywords: Primorsky Dagestan; Early Bronze Age; Kuro-Araxes cultural-historical society; ceramic vessel handles.